A Rare Event of Unmasking Anaplastic Transformation in Pre-Existing Papillary Thyroid Carcinoma - A Case Report - Dr Govardhani V , Dr Kalaivani Amitkumar , Dr Balaji Radhakrishnan , Dr Meethu Rappai (South Eastern European Journal of Public Health, 2025)
Anaplastic thyroid carcinoma (ATC) is a rare, aggressive thyroid cancer accounting for only 1–2% of thyroid cancers but responsible for 14–50% of thyroid cancer-related deaths, with a median survival of 3–5 months. The origin of anaplastic carcinoma remains debated - whether it arises independently or evolves from well-differentiated carcinoma through anaplastic transformation or dedifferentiation, driven by genetic mutations like TP53. It predominantly affects individuals aged 65 and older and is more common in females. Nearly all ATC cases originate within the thyroid gland, rarely arising outside it. The disease is typically locally advanced, invading nearby structures such as blood vessels, skin, and surrounding organs in the neck. Paraneoplastic symptoms may occur. Approximately 50% of patients present with distant metastases, most frequently to the lungs and brain. Diagnosis requires comprehensive sampling, expert pathological interpretation, and additional immunohistochemical and molecular analyses. In our study we have diagnosed, A 65 year male patient with right lobe ATC (Undifferentiated carcinoma) – NOS - major component - predominantly sarcomatoid with other varying patterns. Dedifferentiation from preexisting papillary carcinoma- infiltrating follicular subtype. Right parathyroid gland showing extensive infiltration. This case posits a diagnostic dilemma as there are overlapping features with other thyroid malignancy like medullary thyroid carcinoma- spindle cell variant and poorly differentiated. Careful correlation with clinical details and knowledge of these unique presentations is important for reaching the correct diagnosis. For localized disease diagnosed after primary surgical treatment, adjuvant chemo-radiotherapy is recommended.